The global third way debate - edited by Anthony Giddens (Cambridge Polity Press, 2001)
Left-of-centre governments are currently in power in many countries. In greater or lesser degree, all have moved away from traditional doctrines and policies of the left, recognizing that left values have to be pursued by different means today. The term 'third way' has become a widely accepted, if controversial, label understood by many modernizing social democrats to refer to these attempts at ideological and policy innovation. The debate that has arisen around these developments is a truly world-wide one, stretching from the US and Europe through to Asia, Australasia and Latin America.
Includes bibliographical references and index.
Keywords: Post-communism.